Assessing safety management factors to develop a research agenda for the construction industry. (October 2021) - Newaz, Mohammad Tanvi; Ershadi, Mahmoud; Jefferies, Marcus; Davis, Peter
Abstract: Previous research enables managers to apply appropriate safety management factors for increased site safety. However, the heterogeneity of such factors in contemporary studies makes it difficult for practitioners to keep up to date with relevant alternatives. There is a paucity of systematic reviews that examine factors, map out their relationships, categorize research gaps, assess the practicality of research findings, and offer direction for future research. In this paper, a systematic review of 2574 articles published between 2010 and 2020 and a full-text examination of 75 quantitative surveys were conducted to catalogue, synthesize, and assess safety management factors in contemporary literature. Thematic analysis subsequently revealed 38 interrelated safety management factors to be classified under three individual, workgroup, and organizational groups. A critical content analysis of the representative studies was conducted to identify five future research trends as well as associated research gaps and directions on construction safety management in the form of an agenda suggesting a shift in research emphasis from physical safety issues to organizational and culture-related factors that have the potential to systematically enhance the overall safety performance. Furthermore, directions are provided to safety practitioners concerning the useful implementation of safety management factors.